Open Access

The connection between Hilbert and Hardy inequalities

Journal of Inequalities and Applications20132013:452

https://doi.org/10.1186/1029-242X-2013-452

Received: 10 April 2013

Accepted: 12 September 2013

Published: 7 November 2013

Abstract

In this paper we introduce some new forms of the Hilbert integral inequality, and we study the connection between the obtained inequalities with Hardy inequalities. The reverse form and some applications are also given.

MSC:26D15.

Keywords

Hilbert’s inequalityHölder’s inequalityHardy’s inequality

1 Introduction

The famous Hardy-Hilbert inequality for positive functions f, g and two conjugate parameters p and q such that p > 1 , 1 p + 1 q = 1 is given as
0 0 f ( x ) g ( y ) x + y d x d y < π sin ( π p ) { 0 f p ( x ) d x } 1 p { 0 g q ( x ) d x } 1 q ,
(1.1)
provided that the integrals on the right-hand side are convergent. The constant π sin ( π p ) is best possible [1]. In the last years, inequality (1.1) has been extended in different ways. In [2] the authors obtained the following extension of (1.1):
0 0 f ( x ) g ( y ) ( x + y ) λ d x d y < B ( 1 p A 2 , λ + p A 2 1 ) { 0 x p q A 1 1 f p ( x ) d x } 1 p { 0 y p q A 2 1 g q ( x ) d x } 1 q ,
(1.2)
where B ( 1 p A 2 , λ + p A 2 1 ) is the best possible constant ( B ( x , y ) is the beta function), λ > 0 , A 1 ( 1 λ q , 1 q ) , A 2 ( 1 λ p , 1 p ) and p A 2 + q A 1 = 2 λ . For 0 < p < 1 , 1 p + 1 q = 1 , λ > 0 , A 1 ( 1 q , 1 λ q ) , A 2 ( 1 λ p , 1 p ) and p A 2 + q A 1 = 2 λ , the reverse form of (1.2) is also valid with the same constant factor. In [3] the following extension was given:
a b a b f ( x ) g ( y ) ( a u 2 ( x ) + 2 b u ( x ) v ( y ) + c v 2 ( y ) ) λ d x d y < L { a b u ( x ) p q A 1 1 u ( x ) p 1 f p ( x ) d x } 1 p { a b v ( y ) p q A 2 1 v ( y ) q 1 g q ( y ) d y } 1 q ,
(1.3)
where L = a q A 1 1 2 c p A 2 1 2 B ( 1 p A 2 , 2 λ + p A 2 1 ) F ( 1 p A 2 2 , λ 1 p A 2 2 , λ + 1 2 ; 1 b 2 a c ) is best possible ( F ( α , β ; γ ; x ) is the hypergeometric function), λ > 0 , A 1 ( 1 2 λ q , 1 q ) , A 2 ( 1 2 λ p , 1 p ) and p A 2 + q A 1 = 2 2 λ , a , c > 0 , b 2 < a c , λ > 0 , u and v are differentiable nonnegative strictly increasing functions on ( a , b ) ( a < b ), and they satisfy the following conditions: lim t a + u ( t ) = lim t a + v ( t ) = 0 and lim t b u ( t ) = lim t b v ( t ) = . In particular, if we let a = c = 1 , b = 0 and consider u ( x ) , v ( y ) instead of u ( x ) and v ( y ) respectively in (1.3), we get
a b a b f ( x ) g ( y ) ( u ( x ) + v ( y ) ) λ d x d y < B ( 1 p A 2 , λ + p A 2 1 ) × { a b u ( x ) p q A 1 1 u ( x ) p 1 f p ( x ) d x } 1 p { a b v ( y ) p q A 2 1 v ( y ) q 1 g q ( y ) d y } 1 q ,
(1.4)

here p A 2 + q A 1 = 2 λ as in (1.2).

The following inequalities are special cases of (1.4):
f ( x ) g ( y ) ( e x + e y ) λ d x d y < B ( 1 p A 2 , λ + p A 2 1 ) { e ( p q A 1 p ) x f p ( x ) d x } 1 p { e ( p q A 2 q ) y g q ( y ) d y } 1 q ,
(1.5)
1 1 f ( x ) g ( y ) ( ln x + ln y ) λ d x d y < B ( 1 p A 2 , λ + p A 2 1 ) × { 1 [ ln x ] p q A 1 1 x 1 p f p ( x ) d x } 1 p { 1 [ ln y ] p q A 2 1 y 1 q g q ( y ) d y } 1 q .
(1.6)

Refinements of some Hilbert-type inequalities by virtue of various methods were obtained in [4, 5] and [6]. A survey of some recent results concerning Hilbert and Hilbert-type inequalities can be found in [7] and [8].

If p > 1 , f ( x ) > 0 , and F ( x ) = 0 x f ( t ) d t , then the well-known Hardy inequality [1] is given as
0 ( F ( x ) x ) p d x < ( p p 1 ) p 0 f p ( x ) d x ,
(1.7)
the constant ( p p 1 ) p is best possible. A weighted form of (1.7) was given also by Hardy [1] as
0 x a ( F ( x ) x ) p d x < ( p p 1 a ) p 0 x a f p ( x ) d x ,
(1.8)
where p > 1 , a < p 1 or p < 0 , a > p 1 and the constant ( p p 1 a ) p is best possible. For 0 < p < 1 ( a < p 1 ), inequality (1.8) holds in the reverse direction. Inequality (1.7) was discovered by Hardy while he was trying to introduce a simple proof of Hilbert’s inequality. In the book [9], the following Hardy-type inequality is given:
e k p x ( x f ( t ) d t ) p d x ( k ) p e k p x f p ( x ) d x ,
(1.9)

where k < 0 and p > 1 or p < 0 . If 0 < p < 1 , then the reverse form of (1.9) holds. The constant ( k ) p is best possible.

In [10](see also [9]), the following Hardy-type inequality is obtained for p > 1 :
1 1 x [ ln x ] p ( 1 x f ( t ) d t ) p d x ( p p 1 ) p 1 x p 1 f p ( x ) d x .
(1.10)

For details about inequality (1.7) and its history and development, we refer the reader to the papers [11] and [12].

Recently, in [13], for f , g > 0 , f , g L ( 0 , ) , F ( x ) = 0 x f ( u ) d u and G ( x ) = 0 x g ( u ) d u , λ > 0 , the following form of (1.1) was obtained:
0 0 f ( x ) g ( y ) ( x + y ) λ d x d y λ 2 p q B ( λ q , λ p ) ( 0 x λ 1 F p ( x ) d x ) 1 p ( 0 y λ 1 G q ( y ) d y ) 1 q ,
(1.11)

the constant factor λ 2 p q B ( λ q , λ p ) is best possible. For other Hilbert-type inequalities involving Hardy operators, see, for example, [14] and [15].

In this paper, by estimating the double integral a b a b f ( x ) g ( y ) ( u ( x ) + v ( y ) ) λ d x d y , we introduce an extension of (1.11) with the best constant factor. The reverse form is also obtained. Some applications are given. The connection between Hilbert and Hardy inequalities is also considered. As a consequence of Theorem 3.1, we obtain the following interesting inequality:
0 0 f ( x ) g ( y ) x + y d x d y π p q sin π p ( 0 ( F ( x ) x ) p d x ) 1 p ( 0 ( G ( y ) y ) q d y ) 1 q .

2 Preliminaries and lemmas

Recall that the gamma function Γ ( θ ) and the beta function B ( μ , ν ) are defined respectively by
Γ ( θ ) = 0 t θ 1 e t d t , θ > 0 , B ( μ , ν ) = 0 t μ 1 ( t + 1 ) μ + ν d t , μ , ν > 0 .

In this paper, we assume that u and v are defined as in inequality (1.3) from the introduction.

Lemma 2.1 Let r > 1 , 1 r + 1 s = 1 , φ > 0 , φ L ( a , b ) , Φ ( x ) = a x φ ( u ) d u , and let h be a differentiable nonnegative strictly increasing function on ( a , b ) such that lim x a + h ( x ) = 0 , lim x b h ( x ) = . Then, for t , α > 0 , we have
a b e t h ( x ) φ ( x ) d x t 1 r α Γ ( α s + 1 ) 1 s { a b [ h ( x ) ] α r h ( x ) e t h ( x ) Φ r ( x ) d x } 1 r .
(2.1)
Proof Using integration by parts, we get
a b e t h ( x ) φ ( x ) d x = t a b h ( x ) e t h ( x ) Φ ( x ) d x .
(2.2)
Applying Hölder’s inequality, we obtain
a b h ( x ) e t h ( x ) Φ ( x ) d x = a b ( [ h ( x ) ] α [ h ( x ) ] 1 s e t h ( x ) s ) ( [ h ( x ) ] α [ h ( x ) ] 1 r e t h ( x ) r Φ ( x ) ) d x ( a b [ h ( x ) ] α s h ( x ) e t h ( x ) d x ) 1 s ( a b [ h ( x ) ] α r h ( x ) e t h ( x ) Φ r ( x ) d x ) 1 r = t 1 s α Γ ( α s + 1 ) 1 s ( a b [ h ( x ) ] α r h ( x ) e t h ( x ) Φ r ( x ) d x ) 1 r .

Substituting the last inequality in (2.2), we get (2.1). □

Lemma 2.2 Let 0 < r < 1 , 1 r + 1 s = 1 , φ > 0 , φ L ( a , b ) , Φ ( x ) = a x φ ( u ) d u , and let h be as in Lemma  2.1. Then, for t > 0 and β R ( β s + 1 > 0 ), we have
a b e t h ( x ) φ ( x ) d x t 1 r β Γ ( β s + 1 ) 1 s { a b [ h ( x ) ] β r h ( x ) e t h ( x ) Φ r ( x ) d x } 1 r .
(2.3)
Proof Integration by parts yields
a b e t h ( x ) φ ( x ) d x = t a b h ( x ) e t h ( x ) Φ ( x ) d x .
(2.4)
Using the reverse Hölder inequality, we obtain
a b h ( x ) e t h ( x ) Φ ( x ) d x = a b ( [ h ( x ) ] β [ h ( x ) ] 1 s e t h ( x ) s ) ( [ h ( x ) ] β [ h ( x ) ] 1 r e t h ( x ) r Φ ( x ) ) d x ( a b [ h ( x ) ] β s h ( x ) e t h ( x ) d x ) 1 s ( a b [ h ( x ) ] β r h ( x ) e t h ( x ) Φ r ( x ) d x ) 1 r = t 1 s β Γ ( β s + 1 ) 1 s ( a b [ h ( x ) ] β r h ( x ) e t h ( x ) Φ r ( x ) d x ) 1 r .

Substituting the last inequality in (2.4), we get (2.3).

By the definition of the gamma function above, we may write
1 ( x + y ) λ = 1 Γ ( λ ) 0 t λ 1 e ( x + y ) t d t .
(2.5)

 □

3 Main results

In this section, we introduce two main results in this paper. Theorem 3.1 gives an extended form of inequality (1.11) and it is connected to the famous Hardy inequality. In Theorem 3.2, we introduce the reverse form obtained in Theorem 3.1.

Theorem 3.1 Let p > 1 , 1 p + 1 q = 1 , λ > 0 , γ ( λ p , λ q ) , f , g > 0 , f , g L ( a , b ) , define F ( x ) = a x f ( u ) d u and G ( x ) = a x g ( u ) d u . If a b [ u ( x ) ] λ 1 p γ u ( x ) F p ( x ) d x < and a b [ v ( y ) ] λ 1 + q γ v ( y ) G q ( y ) d y < , then
a b a b f ( x ) g ( y ) ( u ( x ) + v ( y ) ) λ d x d y C ( a b [ u ( x ) ] λ 1 p γ u ( x ) F p ( x ) d x ) 1 p × ( a b [ v ( y ) ] λ 1 + q γ v ( y ) G q ( y ) d y ) 1 q ,
(3.1)

where the constant C = ( λ p + γ ) ( λ q γ ) B ( λ p + γ , λ q γ ) is best possible.

Proof By using (2.5) and applying Hölder’s inequality, we have
I = : a b a b f ( x ) g ( y ) ( u ( x ) + v ( y ) ) λ d x d y = 1 Γ ( λ ) a b a b f ( x ) g ( y ) ( 0 t λ 1 e ( u ( x ) + v ( y ) ) t d t ) d x d y = 1 Γ ( λ ) 0 ( t λ 1 p + γ a b e u ( x ) t f ( x ) d x ) ( t λ 1 q γ a b e v ( y ) t g ( y ) d y ) d t 1 Γ ( λ ) ( 0 t λ 1 + p γ ( a b e u ( x ) t f ( x ) d x ) p d t ) 1 p × ( 0 t λ 1 q γ ( a b e v ( y ) t g ( y ) d y ) q d t ) 1 q .
(3.2)
By Lemma 2.1, for r = p , s = q , α = λ + p γ p q and then for r = q , s = p , α = λ q γ p q , we obtain, respectively,
( a b e u ( x ) t f ( x ) d x ) p t 1 λ + p γ q Γ ( λ p + γ + 1 ) p q a b [ u ( x ) ] λ + p γ q u ( x ) e t u ( x ) F p ( x ) d x , ( a b e v ( y ) t g ( y ) d y ) q t 1 λ q γ p Γ ( λ q γ + 1 ) q p a b [ v ( y ) ] λ q γ p v ( y ) e t v ( y ) G q ( y ) d y .
Substituting these two inequalities in (3.2), we have
I Γ ( λ p + γ + 1 ) 1 q Γ ( λ q γ + 1 ) 1 p Γ ( λ ) ( a b [ u ( x ) ] λ + p γ q u ( x ) F p ( x ) ( 0 t λ p + γ e u ( x ) t d t ) d x ) 1 p × ( a b [ v ( y ) ] λ q γ p v ( y ) G q ( y ) ( 0 t λ q γ e v ( y ) t d t ) d y ) 1 q .
Since
0 t λ p + γ e u ( x ) t d t = [ u ( x ) ] λ p γ 1 Γ ( λ p + γ + 1 )
and
0 t λ q γ e v ( y ) t d t = [ v ( y ) ] λ q + γ 1 Γ ( λ q γ + 1 ) ,
we find
I C ( a b [ u ( x ) ] λ 1 p γ u ( x ) F p ( x ) d x ) 1 p ( a b [ v ( y ) ] λ 1 + q γ v ( y ) G q ( y ) d y ) 1 q .
Now, since Γ ( u + 1 ) = u Γ ( u ) and Γ ( λ p + γ ) Γ ( λ q γ ) Γ ( λ ) = B ( λ p + γ , λ q γ ) , we get
C = ( λ p + γ ) ( λ q γ ) B ( λ p + γ , λ q γ ) .
Inequality (3.1) is proved. We need to show that the constant factor C in (3.1) is best possible. For 0 < ε < min { λ q γ , λ + p γ } , we define the functions f ε ( x ) = 0 , for x ( a , a 1 ) and f ε ( x ) = λ + p γ ε p [ u ( x ) ] λ + p γ ε p 1 u ( x ) for x [ a 1 , b ) and g ε ( y ) = 0 for y ( a , a 2 ) and g ε ( y ) = λ q γ ε q [ v ( y ) ] λ q γ ε q 1 v ( y ) for y [ a 2 , b ) , where a 1 and a 2 are such that u ( a 1 ) = v ( a 2 ) = 1 . Then we get F ε ( x ) = ( [ u ( x ) ] λ + p γ ε p 1 ) for x [ a 1 , b ) and G ε ( y ) = ( [ v ( y ) ] λ q γ ε q 1 ) for y [ a 2 , b ) , F ε ( x ) = G ε ( y ) = 0 for x ( a , a 1 ) , y ( a , a 2 ) , respectively. Suppose that the constant C = ( λ p + γ ) ( λ q γ ) B ( λ p + γ , λ q γ ) is not best possible, then there exists 0 < K < C such that
I K ( a 1 b [ u ( x ) ] λ 1 p γ u ( x ) [ [ u ( x ) ] λ + p γ ε p 1 ] p d x ) 1 p × ( a 2 b [ v ( y ) ] λ 1 + q γ v ( y ) [ [ v ( y ) ] λ q γ ε q 1 ] q d y ) 1 q < K ( a 1 b [ u ( x ) ] ε 1 u ( x ) d x ) 1 p ( a 2 b [ v ( y ) ] ε 1 v ( y ) d y ) 1 q = K ( 1 δ ε 1 d δ ) 1 p ( 1 δ ε 1 d δ ) 1 q = K ε .
(3.3)
On the other hand, we have
I = a b a b f ε ( x ) g ε ( y ) ( u ( x ) + v ( y ) ) λ d x d y = ( λ + p γ ε ) ( λ q γ ε ) p q a 1 b a 2 b [ u ( x ) ] λ + p γ ε p 1 u ( x ) [ v ( y ) ] λ q γ ε q 1 v ( y ) ( u ( x ) + v ( y ) ) λ d y d x = ( λ + p γ ε ) ( λ q γ ε ) p q a 1 b [ u ( x ) ] ε 1 u ( x ) { 1 u ( x ) θ λ q γ ε q 1 ( θ + 1 ) λ d θ } d x = ( λ + p γ ε ) ( λ q γ ε ) p q × { 1 ε 0 θ λ q γ ε q 1 ( θ + 1 ) λ d θ d u a 1 b [ u ( x ) ] ε 1 u ( x ) 0 1 u ( x ) θ λ q γ ε q 1 ( θ + 1 ) λ d θ d x } = ( λ + p γ ε ) ( λ q γ ε ) p q B ( λ p + γ , λ q γ ) + o ( 1 ) ε ( λ + p γ ε ) ( λ q γ ε ) p q a 1 b [ u ( x ) ] ε 1 u ( x ) 0 1 u ( x ) θ λ q γ ε q 1 ( θ + 1 ) λ d θ d x > ( λ + p γ ε ) ( λ q γ ε ) p q B ( λ p + γ , λ q γ ) + o ( 1 ) ε ( λ + p γ ε ) ( λ q γ ε ) p q a 1 b [ u ( x ) ] ε 1 u ( x ) 0 1 u ( x ) θ λ q γ ε q 1 d θ d x = ( λ + p γ ε ) ( λ q γ ε ) p q B ( λ p + γ , λ q γ ) + o ( 1 ) ε O ( 1 ) .
(3.4)

It is obvious that when ε 0 + from (3.3) and (3.4), we obtain a contradiction. Thus, the proof of the theorem is completed. □

Theorem 3.2 Let 0 < p < 1 , 1 p + 1 q = 1 , λ > 0 , γ ( λ p , λ q ) , f , g > 0 , f , g L ( a , b ) , define F ( x ) = a x f ( u ) d u and G ( x ) = a x g ( u ) d u . If a b [ u ( x ) ] λ 1 p γ u ( x ) F p ( x ) d x < and a b [ v ( y ) ] λ 1 + q γ v ( y ) G q ( y ) d y < , then we obtain the reverse form of (3.1) as
a b a b f ( x ) g ( y ) ( u ( x ) + v ( y ) ) λ d x d y C ( a b [ u ( x ) ] λ 1 p γ u ( x ) F p ( x ) d x ) 1 p × ( a b [ v ( y ) ] λ 1 + q γ v ( y ) G q ( y ) d y ) 1 q ,
(3.5)

where C is as in Theorem  3.1.

Proof If we use (2.5) and apply the reverse Hölder inequality, we have
I = : a b a b f ( x ) g ( y ) ( u ( x ) + v ( y ) ) λ d x d y = 1 Γ ( λ ) 0 ( t λ 1 p + γ a b e u ( x ) t f ( x ) d x ) ( t λ 1 q γ a b e v ( y ) t g ( y ) d y ) d t 1 Γ ( λ ) ( 0 t λ 1 + p γ ( a b e u ( x ) t f ( x ) d x ) p d t ) 1 p × ( 0 t λ 1 q γ ( a b e v ( y ) t g ( y ) d y ) q d t ) 1 q .
(3.6)
By Lemma 2.2, for r = p , s = q , β = λ + p γ p q and then for r = q , s = p , β = λ q γ p q , we obtain, respectively,
( a b e u ( x ) t f ( x ) d x ) p t 1 λ + p γ q Γ ( λ p + γ + 1 ) p q a b [ u ( x ) ] λ + p γ q u ( x ) e t u ( x ) F p ( x ) d x , ( a b e v ( y ) t g ( y ) d y ) q t 1 λ q γ p Γ ( λ q γ + 1 ) q p a b [ v ( y ) ] λ q γ p v ( y ) e t v ( y ) G q ( y ) d y .

If we substitute these two inequalities in (3.6) and make some computations as we did in Theorem 3.1, we get inequality (3.5). □

4 Applications

In this section, we give some applications of Theorem 3.1 and Theorem 3.2. We consider some specific functions which satisfy the conditions of the functions u and v, and we see the connection between Hilbert and Hilbert-type inequalities with Hardy and Hardy-type inequalities from the introduction.
  1. 1.
    Let u ( x ) = x , v ( y ) = y , x , y ( 0 , ) , then we find by (3.1)
    0 0 f ( x ) g ( y ) ( x + y ) λ d x d y C ( 0 x λ 1 p γ F p ( x ) d x ) 1 p ( 0 y λ 1 + q γ G q ( y ) d y ) 1 q ,
    (4.1)
    here F ( x ) = 0 x f ( t ) d t and G ( y ) = 0 y g ( t ) d t . If we put γ = 0 in (4.1), we get (1.11). If we let λ = 1 , γ = p 2 p , we obtain the following form:
    0 0 f ( x ) g ( y ) x + y d x d y π p q sin π p ( 0 ( F ( x ) x ) p d x ) 1 p ( 0 ( G ( y ) y ) q d y ) 1 q .
    (4.2)
    Applying Hardy’s inequality (1.7) to the right-hand side of (4.2), we get Hilbert’s inequality (1.1). If we apply the weighted Hardy inequality (1.8) to (4.1), we get
    0 0 f ( x ) g ( y ) ( x + y ) λ d x d y < C 1 ( 0 x p λ 1 p γ f p ( x ) d x ) 1 p ( 0 y q λ 1 + q γ g q ( y ) d y ) 1 q ,
    (4.3)
    where C 1 = B ( λ p + γ , λ q γ ) . Inequality (4.3) is equivalent to inequality (1.2) if we set γ = p λ p q A 1 p ( λ p < γ < λ q ) under the condition p A 2 + q A 1 = 2 λ . By Theorem 3.2, we have the reverse form of (4.1)
    0 0 f ( x ) g ( y ) ( x + y ) λ d x d y C ( 0 x λ 1 p γ F p ( x ) d x ) 1 p ( 0 y λ 1 + q γ G q ( y ) d y ) 1 q .
    (4.4)
    If we apply the reverse inequality of (1.8) to the first integral on the right-hand side in (4.4) and inequality (1.8) to the second integral ( q < 0 ), we get
    0 0 f ( x ) g ( y ) ( x + y ) λ d x d y > C 1 ( 0 x p λ 1 p γ f p ( x ) d x ) 1 p ( 0 y q λ 1 + q γ g q ( y ) d y ) 1 q .
    (4.5)

    Inequality (4.5) is equivalent to the reverse form of (1.2) if we set γ = p λ p q A 1 p under the condition p A 2 + q A 1 = 2 λ .

     
  2. 2.
    If u ( x ) = e x , v ( y ) = e y , x , y ( , ) , we obtain by (3.1)
    f ( x ) g ( y ) ( e x + e y ) λ d x d y C ( e ( λ + p γ ) x F p ( x ) d x ) 1 p ( e ( λ q γ ) y G q ( y ) d y ) 1 q ,
    (4.6)

    here F ( x ) = x f ( t ) d t and G ( y ) = y g ( t ) d t . If we apply (1.9) to the integrals on the right-hand side of (4.6) and set γ = p λ p q A 1 p , we obtain (1.5). The reverse form of (4.6) is also valid, and we may obtain a reverse inequality of (1.5) if we use (1.9) and its reverse form.

     
  3. 3.
    If u ( x ) = ln x , v ( y ) = ln y , x , y ( 1 , ) , then we have
    1 1 f ( x ) g ( y ) ( ln x + ln y ) λ d x d y C ( 1 F p ( x ) x [ ln x ] λ + p γ + 1 d x ) 1 p ( 1 G q ( y ) y [ ln y ] λ q γ + 1 d y ) 1 q ,
    (4.7)
    here F ( x ) = 1 x f ( t ) d t and G ( y ) = 1 y g ( t ) d t . In particular, for λ = 1 , γ = p 2 p , we get
    1 1 f ( x ) g ( y ) ln x + ln y d x d y π p q sin π p ( 1 F p ( x ) x [ ln x ] p d x ) 1 p ( 1 G q ( y ) y [ ln y ] q d y ) 1 q ;

    if we apply (1.10), we get Hilbert-type inequality (1.6).

     

Declarations

Authors’ Affiliations

(1)
Department of Mathematics, Al al-Bayt University

References

  1. Hardy GH, Littlewood JE, Polya G: Inequalities. Cambridge University Press, London; 1952.MATHGoogle Scholar
  2. Krnić M, Mingzhe G, Peĉarić J, Xuemei G: On the best constant in Hilbert’s inequality. Math. Inequal. Appl. 2005, 8(2):317–329.MATHMathSciNetGoogle Scholar
  3. Azar LE: Some extensions of Hilbert’s integral inequality. J. Math. Inequal. 2011, 5(1):131–140.MATHMathSciNetView ArticleGoogle Scholar
  4. Krnić M, Peĉarić J: Extension of Hilbert’s inequality. J. Math. Anal. Appl. 2006, 324: 150–160. 10.1016/j.jmaa.2005.11.069MATHMathSciNetView ArticleGoogle Scholar
  5. Krnić M: A refined discrete Hilbert inequality via the Hermite-Hadamard inequality. Comput. Math. Appl. 2012, 63: 1587–1596. 10.1016/j.camwa.2012.03.014MATHMathSciNetView ArticleGoogle Scholar
  6. Mingzhe G, Yang B: On the extended Hilbert’s inequality. Proc. Am. Math. Soc. 1998, 126: 751–759. 10.1090/S0002-9939-98-04444-XMATHView ArticleGoogle Scholar
  7. Yang B, Rassias TM: On the way of weight coefficients and research for the Hilbert-type inequalities. Math. Inequal. Appl. 2003, 6: 625–658.MATHMathSciNetGoogle Scholar
  8. Yang B: The Norm of Operator and Hilbert-Type Inequalities. Science Press, Beijing; 2009.Google Scholar
  9. Mitrinović DS, Peĉarić JE, Fink AM: Inequalities Involving Functions and Their Integrals and Derivatives. Kluwer Academic, Dordrecht; 1991.MATHView ArticleGoogle Scholar
  10. Chan LY: Some further extensions of Hardy’s inequality. Can. Math. Bull. 1981, 24: 393–400. 10.4153/CMB-1981-061-7MATHView ArticleGoogle Scholar
  11. Kufner A, Maligranda L, Persson L-E: The prehistory of the Hardy inequality. Am. Math. Mon. 2006, 113: 715–732. 10.2307/27642033MATHMathSciNetView ArticleGoogle Scholar
  12. Kufner A, Maligranda L, Persson LE: The Hardy Inequality - About Its History and Some Related Results. Vydavatelský Servis, Pilsen; 2007.MATHGoogle Scholar
  13. Azar, LE: Two new forms of Hilbert integral inequality, Math. Inequal. Appl. (in press)Google Scholar
  14. Adiyasuren V, Batbold T: Some new inequalities similar to Hilbert-type integral inequality with a homogeneous kernel. J. Math. Inequal. 2012, 6: 183–193.MATHMathSciNetView ArticleGoogle Scholar
  15. Adiyasuren V, Batbold T, Krnić M: On several new Hilbert-type inequalities involving means operators. Acta Math. Sin. Engl. Ser. 2013, 29: 1493–1514. 10.1007/s10114-013-2545-xMATHMathSciNetView ArticleGoogle Scholar

Copyright

© Azar; licensee Springer. 2013

This article is published under license to BioMed Central Ltd. This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.